A Biomechanical Comparison of All-Inside Anterior and Posterior Cruciate Ligament Graft Preparation Techniques. Issue 7 (21st July 2017) - Brady, Jacqueline Munch; Skoglund, Kathryn C.; Wichern, Colter R.; O'Sullivan, Joseph G.; Burwell, Anora K.; Nguyen, Joseph T.; Herzka, Andrea
Objectives: The all-inside technique for knee cruciate ligament reconstruction has gained popularity for its potential to preserve tissue and bone stock, and improve visualization during surgery in the setting of a socket vs. a tunnel approach. Various techniques of graft preparation have been described for use in all-inside reconstruction, but to our knowledge no study has compared the various techniques presently being used. This study is a biomechanical comparison of 5 graft preparation techniques used for all-inside cruciate ligament reconstruction, including 2 different methods of quadrupling the graft, and 3 alternative methods used when the available tendon is not long enough to be quadrupled. Methods: Fresh frozen porcine extensor tendons were randomized between 5 groups, including 2 quadrupled groups: Quad-A and Quad-B, and 3 alternative groups: Tripled, Folded, and Two-Doubled, (see Figure 1) with a total N=50. Within each group, 10 specimens were prepared using the designated technique, and subsequently underwent preconditioning (10 loading cycles from 20-50N at 0.1Hz), cyclic loading (500 loading cycles from 50-250N at 1.0Hz) and load-to-failure (applied at 20mm/min). Displacement (mm) and force (N) were measured throughout testing. Cyclic displacement (mm), cyclic stiffness (N/mm), pullout stiffness (N/mm), ultimate failure load (N), and ultimate failure displacement (mm) were the primary endpoints used to compare the grafts. Results: Quad-A and Quad-B demonstrated no significant difference in cyclic displacement (10.51±0.46 and 11.74±0.45, respectively; p >0.05), cyclic stiffness (1086±488.5 and 460.4±71.7, respectively; p >0.05), pullout stiffness (15.87±4.26 and 7.42±4.41, respectively; p >0.05), ultimate failure load (641.2±84.7 and 405.9±237.4, respectively; p >0.05), or ultimate failure displacement (47.35±6.72 and 55.5±0.73, respectively; p >0.05). The Tripled, Folded and Two-Doubled groups differed significantly in terms of cyclic displacement (11.34±0.37, 13.26±0.29 and 28.75±0.83, respectively; p <0.001). There were no significant differences in cyclic stiffness (385.4±48.2, 243.5±36.3 and 210.5±47.2, respectively; p >0.05), pullout stiffness (0.95±0.77, 2.06±2.01 and 1.99±1.62, respectively; p >0.05), ultimate failure load (73.26±59.73, 143.4±140.0 and 128.6±108.3, respectively; p >0.05), or ultimate failure displacement (76.43±0.6, 69.71±0.45 and 55.35±6.06, respectively; p >0.05). Conclusion: The 2 quadrupled techniques demonstrated no significant difference in any of the primary endpoints measured. The 3 alternative methods differed significantly in cyclic displacement, with no significant difference in any other primary endpoints. The Tripled group had the smallest cyclic displacement, followed by the Folded group, and finally, the Two-Doubled group showed greater than twice the cyclic displacement of the other groups. Thus, when surgeons are selecting an alternative graft preparation technique due to insufficient length of the available tendon, the Tripled technique is recommended over the Folded technique, and the Two-Doubled technique is not recommended for use in all-inside cruciate ligament reconstruction. Biomechanical Properties of Graft Constructs Graft Type Cyclic Displacement (mm) Cyclic Stiffness (N/mm) Pullout Stiffness (N/mm) Ultimate Failure Load (N) Ultimate Failure Displacement (mm) Quad-A 10.51 ±0.46 1086 ±488.5 15.86 ± 4.26 641.2 ± 84.7 47.35 ± 6.2 Quad-B 11.74 ±0.45 460.4 ±71.7 7.42 ±4.41 405.9 ±237.4 55.50 ±0.73 Tripled 11.34 ±0.37 ‡§ 385.4 ±48.2 0.95 ±0.77 73.26 ± 59.73 76.43 ±0.60 ‡ Folded 13.26 ± 0.29 †§ 234.5 ± 36.3 2.06 ±2.01 143.4 ± 140.0 69.71 ± 0.45 † Two-Doubled 28.75 ± 0.83 †‡ 210.5 ± 47.2 1.99 ±1.62 128.6 ± 108.3 55.35 ± 6.06 *All data reported as mean ± SEM. Mean significance was set at the 0.05 level: † p < 0.05 compared to Tripled group; ‡ p < 0.05 compared to Folded group; § p < 0.001 compared to Two-Doubled group.